The Educational Context In The Literature Of Ibn Al-Muqaffa Through His Book Al-Adab Al-Saghir/ السياق التربوي في أدب ابْنِ الْمُقَفَّع من خلال كتابه الْأدب الصغير - Almaghzwi, Adel (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The purpose of this study is to analyze the contents of the book